PENGARUH KONSELING KELOMPOK PENDEKATAN ANALISIS TRANSAKSIONAL TERHADAP INTERAKSI SOSIAL SISWA DENGAN TEMAN SEBAYANYA - Rafael Lisinus Ginting; Asiah Asiah; Mutiara Indah Sari Nasution (Universitas Negeri Medan, 2019)
The purpose of this study was to determine the effect of transactional analysis group counseling approach in improving the ability of students' social interaction with their peers. This type of research is quasi-experimental design with one group pre-test and post-test. The subjects in this study were 9 high school students who had low social interaction. The research data were collected using a non-test instrument in the form of a social interaction questionnaire, consisting of 50 valid statements and a reliability level of 0.928. From the analysis results obtained an average student pre-test data = 154.7 including the low category and standard deviation (SDx) = 3.91, while the average student post-test data results = 166.9 including the high and standard deviation categories (SDy) = 531.00. Hypothesis testing using the level test formula marked Wilcoxon obtained the results of J count = 19 and the price of J table = 6. From the table of critical values J for the Wilcoxon level test mark for n = 9, = 0.05 two-way test J 0.05 = 6. Therefore J (19> 6). In accordance with the criteria for acceptance and rejection of the hypothesis, the hypothesis is accepted if Jcount> Jtable. Thus it was stated there was an effect of providing group counseling services to the increase in students' social interaction with peers through the transactional analysis approach. Hypothesis accepted.Keywords: Group Counseling; Transactional Analysis; Social Interactions; Peer Friends; Student